2019
DOI: 10.1242/bio.047183
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of high endoglucanase yields production from polypore fungus, Microporus xanthopus strain KA038 under solid-state fermentation using green tea waste

Abstract: Polypores are diverse macrofungi that have been extensively studied for their lignocellulolytic enzyme production capabilities. Currently, these enzymes are being used for many industrial purposes. However, the high cost associated with their production is the main barrier to their broader application. This work aimed to study the optimal medium and conditions for endoglucanase production using solid state fermentation. Seven polypore strains were used for endoglucanase activity screening. The fermentation exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…The influences of co-cultivation (Metreveli et al 2017), nutrient medium (An et al 2016b), and ion type (Saparrat et al 2010) also have been investigated. Compared to submerged fermentation (SmF), solid-state fermentation (SSF) is a procedure in which the substrate barely appears in water (Nguyen et al 2019). The low moisture content in the fermentation of microorganisms is limited primarily to yeasts, fungi, and bacteria (Acharya et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influences of co-cultivation (Metreveli et al 2017), nutrient medium (An et al 2016b), and ion type (Saparrat et al 2010) also have been investigated. Compared to submerged fermentation (SmF), solid-state fermentation (SSF) is a procedure in which the substrate barely appears in water (Nguyen et al 2019). The low moisture content in the fermentation of microorganisms is limited primarily to yeasts, fungi, and bacteria (Acharya et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fungi are highly adaptable to SSF because the fungal hyphae features are spread across the surface. They easily penetrate inter-particle spaces where their colonization is typically more efficient than other organisms in solid substrates (Sukumaran et al 2005;Nguyen et al 2019). More importantly, using solid state fermentation can help avoid the dilution of enzyme products due to the high content of water in submerged fermentation (Oostra et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The body texture is hard and odorless in smell properties. Boa (2008) and Nguyen et al (2019) reported that several species of Microporus have the potential to be used as drugs.…”
Section: Microporus Spmentioning
confidence: 99%
“…Tekstur tubuh buah Microporus sp. keras dan berbau tanah Nguyen et al (2019). melaporkan bahwa Microporus xanthopus merupakan sumber metabolit sekunder yang berpotensi dimanfaatkan sebagai bahan pengobatan.…”
unclassified